Las caracterizaras del sujeto migrante en los hijos de Alfonso Cuesta y Cuesta - Barva Ramirez, Raúl Gerardo (2016)
for the development of this research work titled "PATIENT CHARACTERISTICS MIGRANTION CHILDREN IN COSTS AND COSTS OF ALFONSO" This general objective: To characterize the migrant subject in the children of Alfonso Cuesta and Cuesta. Also in the development of the thesis the following methods were used: deductive, inductive, historical, analytical, sociological, and the technique of literary analysis is the documentary literature, the same that were of great help to reach the culmination of research work. As a result of the novel have the following characteristics: Economic crisis, in the early thirties of the last century a widespread crisis in the country, greatly affects people of Azuay field, who are forced to migrate between the inner cities of the country , Nambija (East) and Guayaquil; the cuencanas cap straw hat weavers who earn meager income for their hard work, for reasons of time after drought reduce their income, some of the Indians sell their children, many times to pass to serve as the company Children from wealthy families. In the same way I came to the conclusion in the analysis about the migrant subject in offspring that one of the main features is the love of his native land, for example out of the mountains to the coast in search of better job opportunities , abandoning his land and his family; it is an act of nostalgia and memories of migrants who leave their subjects rather than birth. And as a result college students it is recommended reading the work The Children of Alfonso Cuesta and costs because it is an interesting novel about migration and where they can analyze the characteristics of migrants such features are lessons we need to consider each of us to be clear about the problems we face daily, the characteristic features of each migrant. And we also have to investigate whether various sources literary books that talk about the related topic in order to be clear about the message that shows us the author on the subj